EFEKTIVITAS E-LEARNING SEBAGAI MEDIA PEMBELAJARAN MATA KULIAH TEKHNOLOGI TEPAT GUNA DALAM PELAYANAN KEBIDANAN TERHADAP PRESTASI BELAJAR PADA MAHASISWA D-IV KEBIDANAN STIKES AL-INSYIRAH PEKANBARU - Fajar Sari Tanberika (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
Technology is a change in many aspects of life. One of the changes that occur in the world of education is the utilization of information technology as an effective medium in the delivery of learning materials in the form of e-material. Utilization of this information technology has changed the learning model more qualified and efficient. Paper-based learning materials have become electronic based by using electronic devices such as computers and the Internet that are now better known as e-learning. In this quantitative research using sampling technique that is Simple Random Sampling, This research type is Randomized Controlled Trial (RCT).